Potential Implications of Quercetin in Autoimmune Diseases - Shen, Pan; Lin, Weiji; Deng, Xuan; Ba, Xin; Han, Liang; Chen, Zhe; Qin, Kai; Huang, Ying; Tu, Shenghao (Frontiers in Immunology, 2021)
Autoimmune diseases are a worldwide health problem with growing rates of morbidity, and are characterized by breakdown and dysregulation of the immune system. Although their etiology and pathogenesis remain unclear, the application of dietary supplements is gradually increasing in patients with autoimmune diseases, mainly due to their positive effects, relatively safety, and low cost. Quercetin is a natural flavonoid that is widely present in fruits, herbs, and vegetables. It has been shown to have a wide range of beneficial effects and biological activities, including anti-inflammation, anti-oxidation, and neuroprotection. In several recent studies quercetin has reportedly attenuated rheumatoid arthritis, inflammatory bowel disease, multiple sclerosis, and systemic lupus erythematosus in humans or animal models. This review summarizes the evidence for the pharmacological application of quercetin for autoimmune diseases, which supports the view that quercetin may be useful for their prevention and treatment.